BRAND IMAGE, PURCHASE INTENTION & PURCHASE DECISION: STUDI PERILAKU KONSUMEN “KOPI KENANGAN HANYA UNTUKMU “ - Juliyanti, Wiwin; Sidanti, Heny; Purwanto, Hari (AMAL: Jurnal Ekonomi Syariah, 2024)
This research aims to empirically test the influence of brand image on purchasing decisions through purchase intention as an intervening variable for the Kopi Kenangan Hanya Untukmu in Kota Madiun. The research method used is descriptive with a quantitative approach. The research sample consisted of 384 respondents selected using the purposive sampling method. Data collection was carried out through distributing questionnaires using the Google Form platform. Data analysis using SmartPLS 3.0 software. The research results show that brand image has a positive and significant influence on purchasing decisions and purchasing interest in Kopi Kenangan Hanya Untukmu. Apart from that, purchase intention also has a positive and significant effect on purchasing decisions for this product. These findings confirm that brand image has an important role in shaping purchasing interest and ultimately influencing consumer purchasing decisions regarding Kopi Kenangan products. The implication of this research is the importance of the Kopi Kenangan Hanya Untukmu to maintain and improve its brand image in order to strengthen consumer purcahse intention and increase product sales. The contribution of this research is to provide empirical evidence regarding the relationship between brand image, purchasing intention, and purchasing decisions, which can be a basis for marketing decision making in developing branding and promotional strategies for Kopi Kenangan.   Keywords: Brand Image, Purchase Decision, Purchase Intention, Consumer Behavior